Platelet Btk is Required for Maintaining Lung Vascular Integrity during Murine Pneumococcal Pneumosepsis - de Porto, Alexander P. N. A.; Claushuis, Theodora A. M.; van der Donk, Lieve E. H.; de Beer, Regina; de Boer, Onno J.; Florquin, Sandrine; Roelofs, Joris J. T. H.; Hendriks, Rudi W.; van der Poll, Tom; van't Veer, Cornelis; de Vos, Alex F. (Thrombosis and Haemostasis, 2019)
Platelet Bruton's tyrosine kinase (Btk) is an essential signalling protein for the collagen receptor glycoprotein VI (GPVI) and podoplanin receptor C-type-lectin-like receptor-2, which are platelet receptors implicated in the maintenance of vascular integrity during inflammation. Moreover, platelets, platelet GPVI and Btk are important for host defence during murine bacterial pneumosepsis. The aim of this study was to determine the role of platelet Btk in vascular integrity and host defence during murine pneumosepsis caused by the common human pathogens Streptococcus pneumoniae and Klebsiella pneumoniae. Using the Cre-loxP system, male platelet-specific Btk-deficient mice (PF4creBtkfl/Y) were created. Similar to platelets from total Btk-deficient mice, platelets from PF4creBtkfl/Y mice showed abrogated aggregation and P-selectin expression when stimulated with the GPVI ligand cross-linked collagen-related peptide. Upon infection with S. pneumoniae, PF4creBtkfl/Y mice showed increased lung bleeding, but unimpaired anti-bacterial defence. During pneumosepsis evoked by K. pneumoniae, platelet Btk deficiency was not associated with lung bleeding and did not impact on host defence, even when platelet function was further compromised by blocking secondary platelet activation by the P2Y12 receptor antagonist clopidogrel. Together, these data indicate that, while platelet Btk is not important for anti-bacterial defence in pneumosepsis, its role in maintaining vascular integrity in the lung depends on the causative pathogen.
Keywords: Bruton's tyrosine kinase; blood platelets; haemostasis; infection; innate immunity